Learning Discourse Analysis by Applying Metaphorically-Based Materials - Amrin Saragih; Anggraini T Saragih; Muhammad Natsir; Fauziah Khairani Lubis (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
The objective of the study is to investigate the effect of learning Discourse Analysis (DA) by applying metaphorically-based materials. Both the design of qualitative and quantitative study is applied in the present study with 60 student subjects of English Literature Study Program ofthe Faculty of Languages and Arts Universitas Negeri Medan, Indonesia. The subjects were divided into two groups: Experimental and Control Group, each with 30 sudents which is parallel in terms of level of intellectuality and learning facilities. The Control Group studentswere taught the lecture of DA by applying conventional material and model of learning or lecturing whereas the Experimental Group were taught by applying metaphorically-based materials of DA. The students’ achievements were obtained by administering the test and the scores of the two groups were compared and processed by applying t-test at the significance level of a = 0.05 with two-tailed test. It is found that the t-obs value is 2.764 exceeding or being greater than that of the t-tab value of 2.00 (2.764>2.000) where the Ho is rejected implying that the Ha is accepted verifying that learning the lecture of DA is significantly more effective by using metaphorically-based materials than by applying conventional materials or lecturing.